THE EFFECTIVENESS OF GROUP COUNSELING COGNITIVE RESTRUCTURING TECHNIQUES TO REDUCE FEAR OF MISSING OUT (FOMO) IN ADOLESCENT SOCIAL MEDIA USERS IN BAYUNG LENCIR - Fitri, Hartika Utami; Azizah, Ima Maslahatun; Suryati, Suryati (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
Fear of missing out (FoMO) is the behavior of actively accessing social media, continuous access that disturbs the subject, causing feelings of laziness, delays in scheduled activities and concerns about not knowing interesting events that other people are doing. The purpose of this study was to determine the level of fear of missing out (FoMO) in adolescent social media users and the extent to which cognitive restructuring technique group counseling is effective in reducing fear of missing out (FoMO) in adolescent social media users. This type of research is quantitative with an experimental method and uses a one group pretest posttest research design. The population in this study was 77 adolescents with research samples taken using purposive sampling techniques from the results of the pretest treatment, namely 8 people. Furthermore, for data collection techniques, researchers used questionnaires and data analysis techniques were carried out through the Wilcoxon test. The results showed that there was a decrease in the posttest score (high and medium categories with a mean value of 57.5) compared to the pretest results (high and medium categories with a mean value of 75.12). From the data analysis using the Wilcoxon test, it shows that the Zscore value <0.05 with a Zscore value of -2.533, so it can be concluded that group counseling with cognitive restructuring techniques is effective in reducing fear of missing out in adolescents who use social media.